Effectiveness of a bicycle skills training intervention on increasing bicycling and confidence: A longitudinal quasi-experimental study. (September 2019) - Sersli, Stephanie; Scott, Nicholas; Winters, Meghan
Abstract: Background: Bicycling shows potential for addressing both health and transportation challenges. One strategy to encourage more people to bicycle is skills training courses; however, there is limited evidence for their effectiveness, especially longer-term. We assessed the impact of adult bicycle skills training programs offered in Metro Vancouver, Canada, using a longitudinal, quasi-experimental study design to compare changes in bicycling and confidence over time between course participants and a comparison group. Methods: Bicycle courses delivered by accredited instructors, 2 to 4.5 hours in duration, aimed to increase participant comfort level to ride on residential and urban streets through teaching in-person and on-road traffic handling skills. We collected data in 2016 and 2017 through online questionnaires at baseline, 1, 3, and 12 months post-course, and used mixed models to assess changes. Results: We enrolled 135 course and 43 comparison participants. At baseline, 32 participants reported no bicycling; 18 started bicycling during the study. Adjusted models did not find different trajectories for course and comparison participants for bicycling overall (RR=0.99, 95% CI: 0.96, 1.02) or for any specific purpose (commuting RR=1.03, 95% CI: 0.99, 1.08; errands RR=0.97, 95% CI: 0.93, 1.01; leisure RR=0.96, 95% CI: 0.93, 1.00), or for confidence. Conclusion: Bicycle courses aim to address individual-level barriers to bicycling, such as skills, knowledge, and confidence, but such courses may not be enough to overcome other barriers. Bicycle courses should be combined with environmental and other means of support to achieve greater impact on bicycling. Highlights: A short adult bicycle course (2–4.5 h) was associated with a short-term increase in leisure cycling. One year after the course, there were no changes in bicycling for work, errands, or leisure. Without changes to physical and social environments, courses may be insufficient to overcome barriers to bicycling uptake. For lasting impact, augment courses with strategies to maintain routines or complemented with social bicycling opportunities.